An Empirical Investigation on Contract Farming of Medicinal plants and its impact on farmers in Kerala - Ann Mary Jones, Ms.; Vijayan, Sony (International Journal of Psychosocial Rehabilitation, 2020)
The Model Contract Farming Act (2018) is a revolutionary step that promises a win-win situation for both farmers and ayurvedic firms. By entering into a contract farming agreement, the farmers ensure to cultivate medicinal plants according to the specified quantity and quality standards stipulated by the ayurvedic firms. The ayurvedic firms will get supplies of cultivated material of uniform quality, which is otherwise difficult in the case of medicinal plants collected from the forest. In return, farmers receive a fixed remuneration from the company at the time of delivery. It provides an assured market at a pre-agreed price and also promotes sustainable development for rural farmers. The present paper analyses the result of farmer’s perceptions towards contract farming. The Census method was used to collect data, and the population size is 196 farmers. Data was collected from medicinal plant farmers in Thrissur, Malappuram, Palakkad, Wayanad, and Ernakulam districts of Kerala through a structured questionnaire. Using the Statistical Package for Social Sciences, various relevant tests were administered, like factor analysis and multiple regression tests. Based on the reliability test, the minimum value of coefficient alpha (Cronbach’s alpha) obtained was.862.